INCREASING THE EFFICIENCY OF TEACHING THE SCIENCE OF CHEMICAL TECHNOLOGY ON THE BASE OF PEDAGOGICAL TECHNOLOGIES (Academia Science Repository, 2023)
The effectiveness of teaching Chemical Technology is crucial for the development of skilled professionals in the field. This article explores the integration of pedagogical technologies to improve the learning experience and outcomes for students studying Chemical Technology. We discuss various pedagogical approaches, including active learning, collaborative learning, and technology-enhanced learning, and provide recommendations for their implementation in the Chemical Technology curriculum.